2017
DOI: 10.1038/srep46308
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the neutralizing antibody response in chronically HIV-1 CRF07_BC-infected intravenous drug users naïve to antiretroviral therapy

Abstract: Characterizing neutralizing antibody (NAb) responses in individuals infected with diverse HIV-1 strains is necessary to reveal the novel targets for regional preventive and therapeutic strategies development. We evaluated the prevalence, breadth, and potency of NAb responses in 98 CRF07_BC-infected individuals using a large, multi-subtype panel of 30 tier 2-3 Env-pseudotyped viruses. Furthermore, we compared the neutralization pattern of CRF07_BC-infected people with that of subtype B’-infected individuals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A total of 29% of plasma samples neutralized more than 80% of the tested viral strains, and 64% neutralized more than 50% in Chinese individuals infected with HIV-1 clade B 28 . The proportions of neutralizing breadths >80 and 50% were 18 and 53% in CRF07_BC-infected Chinese individuals, respectively 29 . Our group and colleagues identified a monoclonal nAb (DRVIA7) with modest neutralizing breadth from a HIV-1 B-infected Chinese donor, which was the first VRC01-like antibody isolated from Chinese donors and provided an opportunity to investigate the crucial events in the early stages of VRC01-like antibody development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 29% of plasma samples neutralized more than 80% of the tested viral strains, and 64% neutralized more than 50% in Chinese individuals infected with HIV-1 clade B 28 . The proportions of neutralizing breadths >80 and 50% were 18 and 53% in CRF07_BC-infected Chinese individuals, respectively 29 . Our group and colleagues identified a monoclonal nAb (DRVIA7) with modest neutralizing breadth from a HIV-1 B-infected Chinese donor, which was the first VRC01-like antibody isolated from Chinese donors and provided an opportunity to investigate the crucial events in the early stages of VRC01-like antibody development.…”
Section: Discussionmentioning
confidence: 98%
“…A Global Panel of reference Env clones was established by the Montefiori group at Duke University, which facilitated highly standardized assessments of neutralizing antibodies across multiple HIV-1 research platforms in different parts of the world 54 . Another separate panel containing 25 viruses was compiled by the Shao group at the Division of Research on Virology and Immunology (DRVI Panel) of China CDC, which reflected the HIV-1 epidemic in China and has been utilized in previous studies to evaluate neutralizing antibody responses 16 , 28 , 29 . Pseudoviruses HIV-1 BG505_T332N , HIV-1 BJMSM2316_N160K , and HIV-1 BJMSM2316_N332A were generated by site-directed mutagenesis based on HIV-1 BG505 and HIV-1 BJMSM2316 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…During the course of chronic infection, most people living with HIV-1 are eventually capable of making a polyclonal antibody response with at least moderate, but significant, breadth of coverage. Hraber et al reported that *50% of samples from chronically HIV-1-infected individuals neutralized at least 50% of 219 envelope-pseudotyped viruses, and Hu et al reported that 53% of samples from chronically HIV-1-infected individuals neutralized more than 50% of 30 envelope-pseudotyped viruses (41,43). Although immune responses in chronically infected patients cannot clear HIV-1 infections, the induction of similar responses by vaccination before an HIV-1 exposure is expected to be protective.…”
Section: Harnessing Immune Responses Toward Diverse Hiv-1 Envelope Prmentioning
confidence: 99%
“…The HIV-1 Env glycoprotein is highly immunogenic but, in general, the antibodies elicited by it during infection lack neutralizing breadth or potency against primary HIV-1 strains thus failing to inhibit viral replication in infected individuals 1,2 . In natural infection only 5% to 30% of adults develop broadly neutralizing antibodies (bNAbs) after several years of infection 2,3,4,5,6,7 and these bNAbs have little impact in the control of the infection due to the continuous capacity of HIV-1 to diversify and escape these antibodies 5,8,9 . However, some recombinant human bNAbs supress viral replication in HIV-1 infected individuals 10,11,12,13,14,15 , prevent human infection by some HIV-1 strains 16 , and passive immunization in animal models can protect from infection and/or disease progression (reviewed in 17 ).…”
Section: Introductionmentioning
confidence: 99%